2009
DOI: 10.1089/jwh.2008.1285
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension during Pregnancy is Associated with Coronary Artery Calcium Independent of Renal Function

Abstract: Background: Hypertension during pregnancy (HDP) increases the risk of future coronary heart disease (CHD), but it is unknown whether this association is mediated by renal injury. Reduced renal function is both a complication of HDP and a risk factor for CHD. Methods: Logistic regression models were fit to examine the association between a history of HDP and the presence and extent of coronary artery calcification (CAC), a measure of subclinical coronary artery atherosclerosis, in 498 women from the Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Yuan et al [29] show that the most relevant cardiac structural changes observed in pregnancy-associated hypertension are the increase in left atrial and ventricular diameters as well as in the thickness of the inter-ventricular septum with impaired left ventricular diastolic function and sustained systolic function. These results are in agreement with some previous data [18,20,30] as well as with our findings in patients with PEC in whom we observed a preserved systolic function resulting from an increase in both LV end-systolic and end-diastolic volumes. Conversely, we did not observe significant abnormalities in the LV structure of patients with G-PIH, and this is in agreement with the observations of De Conti et al [31] while others [32] have reached different conclusions starting from a lesser systematic classification of hypertension complicating pregnancy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Yuan et al [29] show that the most relevant cardiac structural changes observed in pregnancy-associated hypertension are the increase in left atrial and ventricular diameters as well as in the thickness of the inter-ventricular septum with impaired left ventricular diastolic function and sustained systolic function. These results are in agreement with some previous data [18,20,30] as well as with our findings in patients with PEC in whom we observed a preserved systolic function resulting from an increase in both LV end-systolic and end-diastolic volumes. Conversely, we did not observe significant abnormalities in the LV structure of patients with G-PIH, and this is in agreement with the observations of De Conti et al [31] while others [32] have reached different conclusions starting from a lesser systematic classification of hypertension complicating pregnancy.…”
Section: Discussionsupporting
confidence: 94%
“…In patients with CH, the hemodynamic profile is comparable to that observed in non-pregnant hypertensive patients with limited additional changes of LV structure and function. These data are largely in agreement with the epidemiological evidence demonstrating an increased relative risk of major cardiovascular complications in patients affected by pre-eclampsia or chronic hypertension in pregnancy [20][21][22][23], and support a possible prognostic role for the changes in the hemodynamic and humoral profile of hypertensive pregnancy in addition and beyond blood pressure elevation. Previous studies have evaluated the changes in left ventricular structure and function in pregnant women, and report divergent results [24][25][26][27].…”
Section: Discussionsupporting
confidence: 88%
“…[46,48,[68][69][70][71][72][73] Two retrospective cohort studies have evaluated CACS in women with a history of hypertensive pregnancy disorders, and both found a positive association between CACS and self-reported hypertension in pregnancy. [74,75] There are no published prospective studies yet to evaluate CACS in previous preeclamptic patients. Although CACS is a non-invasive measurement, holds great promise as a CVD risk marker, and provides the most direct evidence for cardiovascular damage, radiation dose and costs should be taken into account when considering CACS for risk assessment.…”
Section: Coronary Artery Calcium Scorementioning
confidence: 99%
“…32 Normal functioning of angiogenic factors, such as VEGF, are critical for maintenance of a healthy, intact endothelium, as demonstrated in animal studies where the lack of one VEGF allele in renal podocytes resulted in characteristic renal lesions seen in preeclampsia. 58 and clinical CVD outcomes. 45,55,57,59,60 In addition, early-onset preeclampsia (before 34 gestational weeks) has been associated with a hazard ratio of 9.5 for CVD death 59 and recurrent disease (ie, in >1 pregnancy) was associated with a 6-fold increase in risk for subsequent hypertension 55 ( Table 2).…”
Section: Pathophysiologic Mechanisms Of Preeclampsia and Vascular Effmentioning
confidence: 99%